Health Education on The Benefits of Rosella Flower Tea Improves Knowledge, Behavior and Blood Pressure. - Alvinna Suci A.P (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Hypertension is a non-communicable disease whose prevalence continues to increase and is often not recognized by sufferers, thus causing the risk of serious complications. This research method uses a descriptive exploratory approach by comparing the knowledge, behavior and blood pressure of Tera exercise participants before and after being educated about the benefits and how to make rosella flower tea (Hibiscus sabdariffa). Respondents in this study were 25 Tera exercise participants, selected by accidental sampling. The results of the activity showed an increase in knowledge in the good category from 20.0% to 52.0%, an increase in behavior in the good category from 8.0% to 80.0%, and an increase in blood pressure in the normal category from 8.0% to 36.0%. The conclusion of this activity shows that respondents' knowledge about complementary therapy of rosella flower tea to improve knowledge, behavior, and help control blood pressure in the group that regularly performs Tera Gymnastics